Pre-Bunking Architecture for Government Public Relations Against Deepfake Disinformation - Yeti Rohayati (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
The rapid development of artificial intelligence (AI) has accelerated the emergence of deepfake technology, creating new challenges for government public communication. Deepfake-based disinformation has the potential to manipulate public perception, undermine institutional credibility, and weaken trust in government information. Existing government public relations approaches remain predominantly reactive, relying on fact-checking, clarification, and debunking mechanisms after false information has already circulated. This study aims to analyse the challenges posed by deepfake-based disinformation to government public communication, examine the limitations of existing public relations approaches, and formulate a pre-bunking architecture as a preventive communication model for government public relations. This research employs a qualitative design with a descriptive-analytical approach. Data were collected through a literature review of scientific journal articles, books, policy reports, and academic publications related to deepfakes, disinformation, digital governance, and strategic communication. The collected data were analysed using qualitative content analysis through classification, interpretation, comparison, and synthesis of relevant findings from previous studies. The results indicate that deepfake disinformation represents a multidimensional threat that challenges information credibility, democratic communication, and institutional legitimacy. Furthermore, existing government public relations strategies are constrained by reactive communication patterns, institutional fragmentation, limited monitoring capabilities, and insufficient public resilience-building initiatives. As a novelty, this study proposes a pre-bunking architecture consisting of four integrated components: early detection and digital monitoring, strategic pre-emptive communication, multi-stakeholder collaboration, and public digital resilience development. This architecture shifts government communication from reactive information management toward anticipatory communication governance capable of strengthening societal resilience against deepfake-based disinformation and sustaining public trust in the digital era.